Comparative evaluation of anti-depressant effects of Citalopram, Ketamine and their combination in animal models of depression: A potential anti-depressant? - Salim Sheikh; Pankaj Sonone; Veena Verma; Chakra Dhar Tripathi; Bushra Ahmed Karim; Girish Gulab Meshram (Open Journal of Pharmacology and Pharmacotherapeutics - Peertechz Publications, 2021)
Background: The prevalence of depression is highest amongst the mood disorders. Nearly one third of the patients suffer from major depression, characterized by increased rate of relapse, residual symptoms and impairment of functionality, along with increased tendency for suicide related behaviour. Therefore, it's very important to acquire and explore in depth knowledge into the etiological aspect of the depression and complementing it with testing of potential newer anti-depression agents. Methods: Evaluation for anti-depressant effect was done in through Tail Suspension Test and Forced Swim Test. Normal saline (control), citalopram, ketamine, and combination of ketamine with citalopram were tested in the 8 groups of mice. Each group comprised of 6 mice. Results: In the TST, on comparison with the control group, the groups treated with citalopram, ketamine and their combination demonstrated a significant (p <0.05) reduction in the immobility time and increase in the time spent in struggle. In the FST, the group treated with citalopram alone showed a non-significant (P >0.05) decrease in the immobility time as compared to the control group.  Conclusion: Ketamine, an NMDA receptor antagonist has anti-depressant effect as evident in both TST & FST models. ketamine or its combination with citalopram was superior to citalopram alone. Not only it has antidepressant effect of its own, it also potentiates the antidepressant effect of citalopram.